Tailored Fabrication of MXene/Chitosan Nanocomposites as Efficient Adsorbents for Heavy Metals Removal from Wastewater - Ibrahim, Yassmin Ahmed Ismail (University of the Witwatersrand, Johannesburg, 2023)
MXene (Ti3C2Tx) has been extensively utilized in water purification systems, including toxic metal ions removal, owing to the unique layered structure and abundant oxygen surface groups. However, challenges such as aggregation and solubility of Ti3C2Tx nanosheets in water have prompted the need for innovative strategies. In this study, we introduce a i3C2Tx-incorporated chitosan matrix (MX/CS) adsorbent designed to address solubility concerns during water treatment. MX/CS adsorbents are tested towards the capture of “cadmium” (Cd 2+) and “Zinc” (Zn2+) ions in aqueous solutions at varied pH values (i.e., acid, neutral and alkaline), initial ions concentrations (25, 50 and 100 ppm), and varied Ti3C2Tx loading (i.e., 1, 5 and 10), to study the optimization adsorption parameters. In addition, the Ti3C2Tx nanosheets were activated/alkalinized at ratio (2:1, i.e., 2MX:OH/CS), where more negative-ions sites are provided, thus, enhancing the preferential sorption for heavy metal ions in terms of high adsorption capacities, and kinetics than the non-activated samples (MX-10/CS). Freundlich isotherms are predominated for the Cd2+ and Zn2+ ions adsorption on both adsorbents. A selectivity study reveals that Zn2+ ions got adsorbed faster on the adsorbents than Cd2+ ions because of its low atomic radii and electronegativity. Finally, the adsorbents will be generated and prepared for additional adsorption cycles to test their stability. The second part of this work is to present the novel fabrication of multifunctional hydrophobic polymeric foam MX nanocomposites for large-scale ultrafast wastewater treatment. Likewise, the foam nanocomposite will be tested for the adoption of multi-ions solution over wide pH rage to demonstrate the applicability of the novel adsorbent for large-scale applications. Overall, this research contributes to the advancement of water treatment technologies by enhancing the stability of MXene-based adsorbents and introducing an innovative fabrication method for hydrophobic polymeric foam MX nanocomposites. The outcomes demonstrate the applicability of these novel adsorbents for efficient and scalable water purification solutions.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: MXene; Chitosan; Composite adsorbents; Water treatment; Heavy metal ions; Hydrophobic polymeric foam; Nanocomposites; Wastewater treatment; SDG-6: Clean water and sanitation